Proposal to Study the Economic and Environmental Benefits of Reducing Soil Erosion in Albania - Bockheim, James (James G. Bockheim, 1997)
This paper is an output of the Land Market Action Plan in Albania, implemented by the Project Management Unit of the Immovable Property Registration System and the Cooperative Working Group, with support from the Government of Albania; from the Land Tenure Center, University of Wisconsin-Madison; from the European Union's PHARE; and from the Terra Institute.
iii, 7 p.
Keywords: Land Protection; Albania; Land Tenure Center; University of Wisconsin--Madison